TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK GADAI (SENDE) SAWAH: (Studi Kasus di Desa Sumbersari Kecamatan Srono Kabupaten Banyuwangi) - Mohamad Al Kafi; Abdul Kholiq Syafaat (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to determine the practice of sende, and to examine the Islamic legal perspective on the practice of sende in Sumbersari Village, Srono District, Banyuwangi Regency. The author employed a qualitative descriptive approach, the analytical tool used in this study was an interactive model. The results obtained from the study regarding the practice of sende in Sumbersari Village. The practice of pawning (sende) for paddy fields is as follows: first, the rahin (the borrower) approaches the murtahin (the mortgagee) to reach an agreement on the amount of debt requested and the paddy field to be used as marhun. After obtaining agreement, the parties to the contract execute the rahn (sende) contract, accompanied by witnesses. The results of the study can be concluded that the practice of pawning (sende) for paddy fields in Sumbersari Village, Srono District, Banyuwangi Regency complies with applicable Islamic law, as it meets Islamic requirements and provisions. The research concludes that the pawning practice using the sende system in Sumbersari Village is legitimate, as it meets the requirements and pillars of rahn, namely: belief in God, the principle of trust in God, and the principle of shighat. It avoids several potential forms of corruption, such as usury and gharar.